The Influence of Social Capital, Entrepreneurial Competence and Entrepreneurial Ecosystem in Shaping Business Incubators in Indonesia - Sucandrawati, Ni Luh Ketut Ayu Sudha; Suartini, Ni Wayan; Wati, Indah; Apriliani, Diah (International Journal of Business, Law, and Education, 2024)
This study looks into how the entrepreneurial ecosystem, social capital, and entrepreneurial competence interact to influence how successful Indonesian business incubators are. Partial Least Squares Structural Equation Modeling (PLS-SEM) was the quantitative method used to examine the data collected from 275 entrepreneurs and incubator stakeholders. The evaluation of the measurement model demonstrated appropriate average variances extracted, strong loadings, and high composite reliabilities, all of which supported the validity and reliability of the selected indicators. Each latent variable's uniqueness was confirmed by discriminant validity analysis. Significant positive correlations between social capital, entrepreneurial competence, the entrepreneurial ecosystem, and the efficacy of business incubators were found by the structural model estimation. The suggested theoretical framework was validated by hypothesis testing, which showed that these elements interact to affect the performance of business incubators in Indonesia. A good fit was shown by the model fit assessment, supporting the structural model's validity. The results enhance our understanding from a theoretical and practical standpoint, offering policymakers, entrepreneurs, and stakeholders a comprehensive framework to maximize the conditions necessary for the success of business incubators.